Analysis of The Influence of Capital, Non-Performing Loans, Efficiency, Liquidity, and Net Income on Profitability - Muslihatun, Annisa; Winarni, Winarni; Santosa, Teguh Budi (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2024)
The study aims to analyze the effect of CAR, NPL, BOPO, LDR, and NIM on Profitability at Bank Neo Commerce simultaneously and partially. The research population is the financial statements of Bank Neo Commerce for the period 2013-2022. The sampling technique used saturated sampling technique and obtained 40 data. The data analysis method uses multiple linear regression. Data analysis techniques using the F Statistical Test, t Statistical Test, and the Coefficient of Determination (R2). The results show CAR, NPL, BOPO, LDR, and NIM simultaneously have a significant effect on ROA Bank Neo Commerce. The t test results show that BOPO and NIM have a significant effect on ROA Bank Neo Commerce. CAR, NPL, and LDR have no significant effect on ROA Bank Neo Commerce. Adjusted R2 of 0.977, shows the contribution of the influence of the independent variable on the dependent variable of 97.7% and the rest is explained by other variables not examined.